2017
DOI: 10.1088/1361-6463/aa7570
|View full text |Cite
|
Sign up to set email alerts
|

State-by-state emission spectra fitting for non-equilibrium plasmas: OH spectra of surface barrier discharge at argon/water interface

Abstract: Abstract. Optical emission spectroscopy applied to non-equilibrium plasmas in molecular gases can give important information on basic plasma parameters, including the rotational, vibrational temperatures and densities of the investigated radiative states. In order to precisely understand the non-equilibrium of rotational-vibrational state distribution from investigated spectra without limiting presumptions, a state-bystate temperature-independent fitting procedure is the ideal approach. In this paper we presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 60 publications
7
93
0
1
Order By: Relevance
“…A schematic diagram of the experimental assembly and images of the generated electric plasma are shown in Figure a‐h. In principle, the SDBD is generated due to high electric field generated in our case by the triple point effect at the common line between air, liquid electrode surface, and tube wall surface . Detailed description and some characteristics of this type of electric discharge can be found in the work of Galmiz et al Technically, any electrically conductive liquid can be used as the liquid electrode, but from the practical standpoint, low conductivity of solution leads to heating of the liquid electrode.…”
Section: Samples Preparations and Used Equipmentmentioning
confidence: 99%
“…A schematic diagram of the experimental assembly and images of the generated electric plasma are shown in Figure a‐h. In principle, the SDBD is generated due to high electric field generated in our case by the triple point effect at the common line between air, liquid electrode surface, and tube wall surface . Detailed description and some characteristics of this type of electric discharge can be found in the work of Galmiz et al Technically, any electrically conductive liquid can be used as the liquid electrode, but from the practical standpoint, low conductivity of solution leads to heating of the liquid electrode.…”
Section: Samples Preparations and Used Equipmentmentioning
confidence: 99%
“…However, in atmospheric-pressure plasmas, we sometimes observe an optical emission spectrum which cannot be fitted by a Boltzmann distribution corresponding to a rotational temperature. To solve the problem in the spectral fitting, Vorac et al developed a state-by-state fitting method and applied it to OH spectra observed in a surface barrier discharge [2].…”
Section: Optical Emission Spectroscopymentioning
confidence: 99%
“…Consequently, neither the N nor the J quantum number is considered "good," but both are "almost good" and can be used to label the rotational states depending on the preference. 1 The relation between the two is J ¼ N AE 1=2 for the fine-structure components, usually labeled 1 and 2, respectively. See Table 1 for summary of the quantum numbers.…”
Section: Structure Of Oh Radical and Its Spectrummentioning
confidence: 99%
“…Here, we have used the standard spectroscopic abbreviation: single prime (N 0 ) is used to describe the upper state of a transition (here exclusively the electronic state A) and double prime (N 00 ) describes the lower state (here exclusively the X electronic state). 1 In this text, we adopt the newer notation with J for the quantum number describing the total angular momentum (apart from the nuclear spin that will be neglected in the whole chapter), N for the total angular momentum apart from the electronic spin, R for pure rotation (seldom used), and S for angular momentum of electronic spin, as in [12,13]. In Herzberg's book, the same quantum numbers are called J, K, N , and S,respectively .…”
Section: Structure Of Oh Radical and Its Spectrummentioning
confidence: 99%
See 1 more Smart Citation